2004
DOI: 10.1152/ajpheart.00671.2003
|View full text |Cite
|
Sign up to set email alerts
|

In vivo role of heme oxygenase in ischemic coronary vasodilation

Abstract: The heart constitutively expresses heme oxygenase (HO)-2, which catabolizes heme-containing proteins to produce biliverdin and carbon monoxide (CO). The heart also contains many possible substrates for HO-2 such as heme groups of myoglobin and cytochrome P-450s, which potentially could be metabolized into CO. As a result of observations that CO activates guanylyl cyclase and induces vascular relaxation and that HO appears to confer protection from ischemic injury, we hypothesized that the HO-CO pathway is invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 46 publications
0
21
1
Order By: Relevance
“…On the other hand, HO-1 could potentially maintain or improve cardiac performance by reducing coronary vascular tone. HO-derived CO activates soluble guanylate cyclase analogous to nitric oxide and has been reported to contribute to ischemia-induced vasodilation in dogs (38). Furthermore, bilirubin improved postischemic LV functional recovery in isolated rat hearts subjected to global ischemia (21).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, HO-1 could potentially maintain or improve cardiac performance by reducing coronary vascular tone. HO-derived CO activates soluble guanylate cyclase analogous to nitric oxide and has been reported to contribute to ischemia-induced vasodilation in dogs (38). Furthermore, bilirubin improved postischemic LV functional recovery in isolated rat hearts subjected to global ischemia (21).…”
Section: Discussionmentioning
confidence: 99%
“…The HO-CO pathway is involved in ischemic vasodilation in the coronary microcirculation (Nishikawa et al, 2004). The occurrence of severe right ventricular enlargement after chronic hypoxia was shown in HO-1-deficient compared with wild-type mice (Yet et al, 1999) and the cardiac-specific expression of HO-1 protected against ischemia and reperfusion .…”
Section: F Heme Oxygenase-1 In Myocardial Ischemiareperfusion Injurymentioning
confidence: 99%
“…It has been reported that HO-2 activation occurs in ischemic hearts in dogs and that inhibition of the HO HEME OXYGENASE AND PHARMACOLOGICAL/DRUG DEVELOPMENT system inhibits vasodilation during ischemia in the presence of NO and COX inhibitors (Nishikawa et al, 2004). CORM-3 prevents ischemic damage (Guo et al, 2004).…”
Section: F Heme Oxygenase-1 In Myocardial Ischemiareperfusion Injurymentioning
confidence: 99%
“…In sheep during hypoxemia, a decrease in PVR was shown after inhalation of CO (Nachar et al, 2001). Investigation of the coronary microcirculation in dog hearts in vivo showed that during ischemia HO activation caused dilatation, but only when other systems such as NO, prostaglandins and K + channels where impaired (Nishikawa, Stepp, Merkus, Jones, & Chilian, 2004).…”
Section: Circulationmentioning
confidence: 99%
“…Perhaps when CO is administrated, less NO is produced resulting in unaltered vascular tone. Accordingly, one finding in vivo showed an effect of CO only when the NO system was inhibited (Nishikawa et al, 2004).…”
Section: Paper IImentioning
confidence: 99%